5D black hole solution in Einstein-Yang-Mills-Gauss-Bonnet theory - Mazharimousavi, S. Habib; Halilsoy, M. (Amer Physical Soc, 2007)
By adopting the 5D version of the Wu-Yang ansatz we present in closed form a black hole solution in the Einstein-Yang-Mills-Gauss-Bonnet theory. In the Einstein-Yang-Mills limit, we recover the 5D black hole solution already known.